Trajectory analysis of Polar Patrol Balloon (PPB) flights in the stratosphere over Antarctica in summer and spring: A preliminary result - Kanzawa, Hiroshi; Yamazaki, Koji; Yamanaka, Manabu D.; Fujii, Ryoichi (1994)
Actual trajectories of two PPB's which flew in the Antarctic stratosphere in austral summer and spring are compared with those calculated based on objective analysis data of Japan Meteorological Agency (JMA). The differences between the actual and calculated trajectories are discussed to check reliability of the JMA objective analysis data for the stratosphere, and to detect subsynoptic scale variability due to gravity waves and others.